Falling up [videorecording (DVD)] - Rosenthal, David M.; O'Toole, Annette, 1953-; Pantoliano, Joe; Cross, Joseph; Rogers, Mimi; Cook, Rachael Leigh, 1979-; Roemer, Sarah; Snoop Dogg, 1972- (Anchor Bay Entertainment, 2010)
Henry O'Shea is on his way to a nursing degree until his father's sudden death forces him to take a job as a doorman in an elite Manhattan apartment building. Against the warning of his boss and co-worker, he ends up falling for the beautiful daughter of one of the wealthiest tenant's in the building. Can a romance between a regular Joe and a 5th Avenue girl make it past the front door?